Making it long: men, women, and the great American novel now. Issue 2 (7th February 2019) - Boddy, Kasia
ABSTRACT: In 2010, following the publication of Jonathan Franzen's fourth novel, Freedom, a furore briefly emerged in the literary media about whether the Great American Novel, so-called since 1868, is 'coded male'. This essay briefly explores the history of novelistic claims to national spokesmanship, and, latterly, spokeswomanship. It considers the influence on Don DeLillo on contemporary fiction, and particularly, his importance for women writers such as Jennifer Egan, Dana Spiotta, Rachel Kushner and A.M. Homes. The bulk of the essay offers a reading of Homes's 2013 novel May We Be Forgiven, which simultaneously critiques the macho posturings of the GAN and asserts its place within that tradition.